Hotel privacy management and guest trust building: a relational signaling perspective - Moon, Hyoungeun; Yu, Jongsik; Chua, Bee Lia; Han, Heesup (Elsevier, 2022)
By using the tenets of relational signaling theory, this study proposes a conceptual model that investigates the effect of hotel privacy management (thin trust) on guests’ cognitive and affective trust (thick trust), which influences guest intention to accept personal information collection and switch to another hotel. Survey data was collected online and analyzed by using confirmatory factory analysis and structural equation modeling. The results reveal that hotels’ privacy policy, privacy assurance, and employees' information access control are the key factors forming guests’ cognitive and affective trust. While both cognitive and affective trust increase guests’ intention to accept information collection by hotels, only cognitive trust significantly decreases guests’ switching intention. This study also reveals that when hotels hold weaker reputation both cognitive and affective trust play a critical role in increasing guests’ acceptance of hotel information collection. Theoretical implications to the privacy-related literature and practical implications to hotel practitioners are discussed.